Personal Branding Sebagai Peningkatan Jumlah Streams Karya Musik Suara Kayu - Gea, Joanito; Nurjanah, Siti (Research and Community Service UNIVERSITAS KALBIS, 2024)
This research aims to analyze the application of personal branding as a digital marketing strategy for the music group Suara Kayu. The research method used is qualitative with a case study approach, involving in-depth interviews, observations, and related literature analysis. The results show that strong personal branding can enhance the attractiveness and recognition of the music group on digital platforms, increase fan interaction, and expand market reach. Suara Kayu has successfully built a consistent and authentic image through creative content and active social media interaction, which positively contributes to their digital marketing strategy. This study provides valuable insights for musicians and music marketing managers in developing effective personal branding communication in the digital era.